Assessment of the sentiments expressed by traumatic brain injury patients and caregivers: A qualitative study based on in-depth interviews - Raquel Mena-Marcos; Eleuterio A. Sánchez-Romero; Blanca Navarro-Main; Alfonso Lagares-Gómez-Abascal; Laura Jiménez-Ortega; Juan Nicolás Cuenca-Zaldívar (Heliyon)
Introduction: Traumatic Brain Injury (TBI) is a significant public health concern that causes death, disability, and economic burden. Its repercussions affect physical, cognitive, emotional, and behavioral aspects of long-term care needs. Despite improvements in communication among multidisciplinary teams, the management of TBI remains fragmented. Objective: This study aimed to assess patients and caregivers’ experiences through sentiment analysis. Materials and methods: A qualitative cross-sectional study utilized structured topic modeling (STM) to analyze in-depth interview data. The study involved 29 patients with TBI and 27 caregivers in Madrid (Spain), using a survey design. The interviews were conducted, transcribed, and coded independently over 5 months. Sentiments such as anticipation, fear, and emotional concerns were analyzed using three dictionaries. The STM analysis identified four key concepts: desire for independence, potential improvement, need for injury information, and psychological consequences. STM diagnostic graphs were used to determine the number of topics relevant to the evaluation of patient and caregiver concerns. Furthermore, an analysis was conducted across four topics. Results: The average age of the patients was 44.2 ± 14.9 years (69 % males). Regarding TBI severity, 59 % of patients had severe TBI, whereas the remaining 41 % had experienced moderate TBI. Among the caregivers, the majority were parents (30 %), partners (24 %), or siblings (24 % each). Among the 51 participants, sentiments were analyzed using three dictionaries. While there were no significant age differences (Z = 0.24, p = 0.815), the STM model was adjusted for significant sex differences (p = 0.017) between patients and relatives. Anticipation and fear prevailed in both groups, highlighting the shared emotional patterns. Discussion: The analysis of diagnostic graphs indicated the optimal number of topics for evaluation, emphasizing key concerns across different phases of TBI. Patients' main worries shifted from physical symptoms to limitations in daily life and independence. Caregivers highlighted the importance of staff interactions, misinformation challenges, and the need for psychological care. Conclusion: Key patient concerns, including dependency on daily activities, limitations in autonomy, and caregiver burden, emphasize crucial areas for enhancement in multidisciplinary treatment. Moreover, the lack of long-term psychological support is a significant barrier to optimal patient and caregiver well-being.